Elementary behaviour of composite steel and concrete structural members - Oehlers, Deric J.
This book is aimed at developing elementary analysis skills, familiarity and an intuitive feel for composite construction that is required by undergraduate and graduate students, and by structural engineers. It does not require a prior knowledge of advanced analysis and design techniques, and builds on simple concepts such as statics and the mechanics of materials. A topic is first introduced by a brief description, with numerous carefully-chosen examples forming an integral part of the main text. Working through the examples allows the reader to gain a full understanding of the subject, as a.